Desifter Interventions: Heaven, Home, and Habit Approaches - Prasetya, Ardi Putra; Meliala, Adrianus Eliasta Sembiring; Sulhin, Iqrak (Technium Social Sciences Journal, 2022)
In this study, the author will explain how efforts to prevent recidivism and encourage former perpetrators of terror to desistance from terrorism. The study sought to answer the question: "What is needed to improve the situation of desistance from terrorism?". Researchers will use a triple H (Head, Heart, and Hands) approach to answer the study question. The discussion in this study began with explaining the current conditions of heaven, home, and habit elements, which are based on the findings of the focus group discussion. After knowing and explaining the current condition by finding the root of the problem, the next section of the researcher describes the intervention based on the root of the problem so that the intervention centers on handling and countering current and future conditions. The discussion in this study is also focused on developing a conceptual framework that aims to be a guideline to explain the current conditions for the prevention of recidivism and encourage former perpetrators of terror in situations of desistance from terrorism. Thus, government policyholders and agencies can focus on developing prevention and handling strategies based on heaven, habit, and home concepts.